Психофизиологическая оценка эффективности реабилитации пожарных – спасателей - Чумаева, Ю.В. (Актуальні проблеми транспортної медицини, 2008)
Проаналізована система реабілітації пожежників – рятувальників з погляду психофізіології. Показано, що модель і зміст обстеження, узяті з практики профвідбору, можуть бути використані лише частково. Фактично з більше ніж 30 вивчених показників лише 10 виявили достовірні відмінності до і після реабілітації. Необхідно об’єднати зусилля і досвід фахівців різних рівнів в області медицини, психології і психофізіології з метою створення оптимальної і ефективної системи реабілітації. The system of firemen rescuers rehabilitation is analysed from the point of view of psychophysiology. It is shown, that model and the maintenance of studies taken from the occupational psychophysiological selection practice, can be used only in part in such examinations. Actually from more than 30 investigated parameters only 10 have revealed authentic differences before rehabilitation. It is necessary to unit efforts and experience of experts of various levels in the field of medicine, psychologies and psychophysiology with the purpose of creation of optimum and effective system of rehabilitation.